Compound hydrophobic transparent fireproof coating for shutters
By modifying calcium-based bentonite with amidino urea phosphate, an interlayer modified calcium-based bentonite flame retardant is prepared and combined with other components to form a composite hydrophobic transparent shutter fire-retardant coating, which solves the problem of poor fire-retardant effects of traditional fire-retardant coatings and significantly improves the hydrophobicity and fire-retardant properties of the shutters.
Patent Information
- Application Number
- CN202510038919.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional single-type fire-retardant coatings have the problem of poor fire resistance in blind applications, which is difficult to meet the efficient fireproof and hydrophobic needs of blinds.
Calcium-based bentonite is modified by amidino urea phosphate, and an interlayer modified calcium-based bentonite flame retardant is prepared, and it is compounded with other components such as acrylic resin, water glass, silane coupling agent, etc. to form a composite hydrophobic transparent shutter fire-retardant coating.
It significantly improves the hydrophobicity and fire-retardant properties of the blind blades, enhances the thermal stability and flame-retardant properties of the paint, delays the combustion speed, and reduces the damage caused by the fire to buildings and internal items.
Smart Images

Figure CN119799094A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fire retardant coatings, and in particular relates to a compound hydrophobic transparent shutter fire retardant coating. Background Art
[0002] Venetian blinds are a common type of window that consists of many horizontal blades, which are usually made of materials such as wood, metal or plastic. The main function of Venetian blinds is to control light and ventilation by turning or adjusting the angle of the blades, and they also have a good shading effect. The main reason why Venetian blinds need to be fire-resistant and flame-retardant is that when a fire occurs, the blinds can effectively prevent the spread of the fire, buy precious time for the evacuation of personnel, and ensure life safety. In addition, fire-resistant and flame-retardant can also reduce the damage to buildings and internal items caused by fire, and reduce the economic losses caused by fire. At the same time, meeting building safety standards is also an important reason for the fire-resistant and flame-retardant properties of Venetian blinds. The hydrophobicity of Venetian blinds is also very important. On the one hand, hydrophobicity can prevent moisture from accumulating on the surface of the blinds, avoid problems such as wood rotting and metal rusting caused by moisture erosion, and extend the service life of the blinds. On the other hand, keeping the surface of the blinds dry can improve the user experience, avoid odors and mildew caused by moisture, and prevent water spots and stains from forming on the surface of the blinds, keeping them beautiful and tidy. Therefore, coatings are often needed to improve the hydrophobicity and fire-resistant properties of blinds. However, the traditional single-type fire retardant coating has the defect of poor fire retardant effect, so there is a need for a more efficient, environmentally friendly fire retardant coating that can meet the special needs of blinds. Summary of the invention
[0003] In view of the above situation, in order to overcome the defects of the prior art, the present invention modifies calcium-based bentonite by guanyl phosphate urea, and then prepares an intercalated modified calcium-based bentonite flame retardant, which is applied to the production of blinds to improve the hydrophobicity and fire retardancy of blinds blades.
[0004] In order to achieve the above-mentioned purpose, the following technical scheme is adopted: The present invention provides a compound hydrophobic transparent fire-retardant coating for venetian blinds, comprising the following components in parts by weight: 15-25 parts of acrylic resin, 3-5 parts of water glass, 2-5 parts of potassium silicate, 3-8 parts of silane coupling agent, 2-6 parts of wetting agent, 1-3 parts of buffer, 3-7 parts of film-forming aid, 5-10 parts of nano-silica, 10-20 parts of intercalated modified calcium-based bentonite flame retardant, and 80-100 parts of deionized water.
[0005] The intercalation modified calcium-based bentonite flame retardant is prepared by the following steps:
[0006] a. Add calcium bentonite to deionized water, stir for 5-10 minutes to evenly disperse the modified bentonite to form a 1-3g / L calcium bentonite suspension, add guanyl urea phosphate to deionized water to obtain a 0.8-1.2g / L guanyl urea phosphate solution, and then place the suspension in a constant temperature water bath at 80°C, slowly dropwise add the guanyl urea phosphate solution under the assistance of ultrasound, react for 2-5 hours, obtain a precipitate, filter out the precipitate, dry it in a vacuum oven at 70-90°C for 12-24 hours, and then grind it into powder, pass it through a 200-mesh sieve, and obtain intercalated modified calcium bentonite;
[0007] b. The intercalated modified calcium-based bentonite is crushed, mixed with epoxy resin, stirred and heated to 100-120°C, mixed evenly and returned to room temperature, then a curing agent and an accelerator are added, stirred evenly, ultrasonically dispersed for 15-30 minutes, defoamed in a vacuum oven at 70-90°C for 1-3 hours, then cast, demolded, crushed into powder, and sieved through a 200-mesh sieve to obtain the intercalated modified calcium-based bentonite flame retardant.
[0008] Furthermore, in the step a, the mass ratio of the calcium bentonite suspension to the guanyl phosphate urea solution is 1:2-5.
[0009] Furthermore, in the step b, the mass ratio of the intercalated modified calcium-based bentonite, epoxy resin, curing agent and accelerator is 5-10:1-3:0.1-0.5:0.5-1.
[0010] Furthermore, the silane coupling agent is one or more of γ-glycidyl trimethoxy silane, γ-aminopropyl triethoxy silane, γ-methacryloxypropyl trimethoxy silane and 3-aminopropyl trimethoxy silane.
[0011] Furthermore, the wetting agent is one or more of ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, polyether-modified silicone, polysorbate, nonylphenol polyoxyethylene ether and octylphenol polyoxyethylene ether.
[0012] Furthermore, the buffer is one or more of EDTA, disodium EDTA, diethanolamine and triethanolamine.
[0013] Furthermore, the film-forming aid is one or more of propylene glycol methyl ether, dipropylene glycol butyl ether, N,N-dimethylformamide and isobutyl alcohol.
[0014] Furthermore, the curing agent is one of methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride and trimellitic anhydride glyceride.
[0015] Furthermore, the accelerator is one of triethylenetetramine, diethylenetriamine, N,N-dimethylaniline and N,N-dimethylbenzylamine.
[0016] Furthermore, the fire retardant coating is used in the production of semi-finished products of venetian blinds, including the following steps: putting solid wood chips into a high-temperature tank, soaking them in the fire retardant coating for 10 hours, then taking the wood chips out of the tank, and then performing processes such as drying, sorting, cutting, rolling, puttying, and painting to complete the production of the venetian blinds.
[0017] The beneficial effects of the present invention are as follows: the present invention performs modification treatment on calcium-based bentonite by guanyl urea phosphate to prepare guanyl urea phosphate intercalated calcium-based bentonite, guanyl urea phosphate groups undergo ion exchange between calcium-based bentonite layers, thereby increasing the interlayer spacing of the calcium-based bentonite and greatly improving the thermal stability of the coating; due to the increase in the interlayer spacing of the calcium-based bentonite, a more stable carbon layer can be formed during the combustion process; when a fire occurs, the carbon layer can effectively prevent heat transfer and slow down the combustion rate, thereby improving the flame retardant effect; at the same time, the flame retardant has the synergistic flame retardant effect of nitrogen-phosphorus flame retardant and calcium-based bentonite, thereby further enhancing the flame retardant performance; the silane coupling agent in the coating can form a layer of compact hydrophobic structure on the surface of the coating, thereby making the surface of the coating have good hydrophobic performance; and nano-silicon dioxide also helps to improve the hydrophobicity of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The oxygen index test results of the fire retardant coatings prepared in various embodiments and comparative examples of the present invention are shown.
[0019] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0022] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0023] Example 1
[0024] A composite hydrophobic transparent fire-retardant coating for venetian blinds comprises the following components in parts by weight: 25 parts of acrylic resin, 5 parts of water glass, 5 parts of potassium silicate, 8 parts of silane coupling agent, 6 parts of wetting agent, 3 parts of buffer, 7 parts of film-forming aid, 10 parts of nano-silicon dioxide, 20 parts of intercalated modified calcium-based bentonite flame retardant and 100 parts of deionized water.
[0025] The intercalation modified calcium-based bentonite flame retardant is prepared by the following steps:
[0026] a. Add calcium bentonite to deionized water, stir for 10 minutes to evenly disperse the modified bentonite to form a 3g / L calcium bentonite suspension, add guanyl urea phosphate to deionized water to obtain a 1.2g / L guanyl urea phosphate solution, and then place the suspension in a constant temperature water bath at 80°C. Under the assistance of ultrasound, slowly drop the guanyl urea phosphate solution. After reacting for 5 hours, a precipitate is obtained. The precipitate is filtered out, dried in a vacuum oven at 90°C for 24 hours, and then ground into powder, and passed through a 200-mesh sieve to obtain intercalated modified calcium bentonite;
[0027] b. The intercalated modified calcium-based bentonite is crushed, mixed with epoxy resin, heated to 120°C with stirring, returned to room temperature after mixing evenly, and then a curing agent and an accelerator are added. After stirring evenly, ultrasonic dispersion is performed for 30 minutes, and the mixture is defoamed in a vacuum oven at 90°C for 3 hours. The mixture is then cast, demolded, crushed into powder, and sieved through a 200-mesh sieve to obtain the intercalated modified calcium-based bentonite flame retardant.
[0028] The mass ratio of the calcium-based bentonite suspension to the guanyl urea phosphate solution in step a is 1:5.
[0029] In the step b, the mass ratio of intercalated modified calcium-based bentonite, epoxy resin, curing agent and accelerator is 10:3:0.5:1.
[0030] The silane coupling agent is a mixture of γ-glycidyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane and 3-aminopropyl trimethoxysilane in a mass ratio of 2:2:1:2; the wetting agent is a mixture of ethylene glycol monobutyl ether, polysorbate, nonylphenol polyoxyethylene ether and octylphenol polyoxyethylene ether in a mass ratio of 1:2:1:1; the buffer is a mixture of EDTA, disodium EDTA, diethanolamine and triethanolamine in a mass ratio of 1:1:1:2; the film-forming aid is a mixture of propylene glycol methyl ether, dipropylene glycol butyl ether, N,N-dimethylformamide and isobutyl alcohol in a mass ratio of 1:1:1:1; the curing agent is methyltetrahydrophthalic anhydride; and the accelerator is triethylenetetramine.
[0031] Example 2
[0032] A composite hydrophobic transparent fire-retardant coating for venetian blinds comprises the following components in parts by weight: 15 parts of acrylic resin, 3 parts of water glass, 2 parts of potassium silicate, 3 parts of silane coupling agent, 2 parts of wetting agent, 1 part of buffer, 3 parts of film-forming aid, 5 parts of nano-silicon dioxide, 10 parts of intercalated modified calcium-based bentonite flame retardant and 80 parts of deionized water.
[0033] The intercalation modified calcium-based bentonite flame retardant is prepared by the following steps:
[0034] a. Add calcium bentonite to deionized water, stir for 5 minutes to evenly disperse the modified bentonite to form a 1g / L calcium bentonite suspension, add guanyl urea phosphate to deionized water to obtain a 0.8g / L guanyl urea phosphate solution, and then place the suspension in a constant temperature water bath at 80°C. Under the assistance of ultrasound, slowly drop the guanyl urea phosphate solution. After reacting for 2 hours, a precipitate is obtained. The precipitate is filtered out, dried in a vacuum oven at 70°C for 12 hours, and then ground into powder, passed through a 200-mesh sieve, and intercalated modified calcium bentonite is obtained;
[0035] b. The intercalated modified calcium-based bentonite is crushed, mixed with epoxy resin, heated to 100°C with stirring, returned to room temperature after mixing evenly, and then a curing agent and an accelerator are added. After stirring evenly, ultrasonic dispersion is performed for 15 minutes, and the mixture is defoamed in a vacuum oven at 70°C for 1 hour. The mixture is then cast, demolded, crushed into powder, and sieved through a 200-mesh sieve to obtain the intercalated modified calcium-based bentonite flame retardant.
[0036] The mass ratio of the calcium-based bentonite suspension to the guanyl phosphate urea solution in step a is 1:2.
[0037] In the step b, the mass ratio of intercalated modified calcium-based bentonite, epoxy resin, curing agent and accelerator is 5:1:0.1:0.5.
[0038] The silane coupling agent is γ-glycidyl trimethoxysilane; the wetting agent is ethylene glycol monobutyl ether; the buffer is EDTA; the film-forming aid is propylene glycol methyl ether; the curing agent is hexahydrophthalic anhydride; and the accelerator is diethylenetriamine.
[0039] Example 3
[0040] A composite hydrophobic transparent fire-retardant coating for venetian blinds comprises the following components in parts by weight: 20 parts of acrylic resin, 4 parts of water glass, 3 parts of potassium silicate, 5 parts of silane coupling agent, 4 parts of wetting agent, 2 parts of buffer, 5 parts of film-forming aid, 8 parts of nano-silicon dioxide, 15 parts of intercalated modified calcium-based bentonite flame retardant and 90 parts of deionized water.
[0041] The intercalation modified calcium-based bentonite flame retardant is prepared by the following steps:
[0042] a. Add calcium bentonite to deionized water, stir for 8 minutes to evenly disperse the modified bentonite to form a 2g / L calcium bentonite suspension, add guanyl urea phosphate to deionized water to obtain a 1g / L guanyl urea phosphate solution, and then place the suspension in a constant temperature water bath at 80°C, slowly drop the guanyl urea phosphate solution under the assistance of ultrasound, react for 3 hours to obtain a precipitate, filter the precipitate, dry it in a vacuum oven at 80°C for 18 hours, and then grind it into powder, pass it through a 200-mesh sieve to obtain intercalated modified calcium bentonite;
[0043] b. The intercalated modified calcium-based bentonite is crushed, mixed with epoxy resin, heated to 110°C with stirring, returned to room temperature after mixing evenly, and then a curing agent and an accelerator are added. After stirring evenly, ultrasonic dispersion is performed for 20 minutes, and the mixture is defoamed in a vacuum oven at 80°C for 2 hours. The mixture is then cast, demolded, crushed into powder, and sieved through a 200-mesh sieve to obtain the intercalated modified calcium-based bentonite flame retardant.
[0044] The mass ratio of the calcium-based bentonite suspension to the guanyl phosphate urea solution in step a is 1:3.5.
[0045] The mass ratio of intercalation modified calcium-based bentonite, epoxy resin, curing agent and accelerator in step b is:
[0046]
[0047] The silane coupling agent is a mixture of γ-glycidyl trimethoxysilane and γ-aminopropyl triethoxysilane in a mass ratio of 2:1; the wetting agent is a mixture of polyether-modified silicone, polysorbate, nonylphenol polyoxyethylene ether and octylphenol polyoxyethylene ether in a mass ratio of 2:3:1:1; the buffer is a mixture of disodium EDTA and diethanolamine in a mass ratio of 1:3; the film-forming aid is a mixture of dipropylene glycol butyl ether, N,N-dimethylformamide and isobutyl alcohol in a mass ratio of 2:3:1; the curing agent is trimellitic anhydride glyceride; and the accelerator is N,N-dimethylaniline.
[0048] Comparative Example 1
[0049] In this comparative example, an equal amount of calcium-based bentonite is used to replace the intercalated modified calcium-based bentonite flame retardant, and the rest is the same as Example 3.
[0050] Comparative Example 2
[0051] In this comparative example, an equal amount of guanyl phosphate urea is used to replace the intercalated modified calcium-based bentonite flame retardant, and the rest is the same as Example 3.
[0052] Comparative Example 2
[0053] The coating in this comparative example does not contain the intercalated modified calcium-based bentonite flame retardant, and the rest is the same as Example 3.
[0054] Results Analysis
[0055] The oxygen index of the fire retardant coatings of Examples 1-3 and Comparative Examples 1-3 was measured using a JF-5 fully automatic oxygen index tester. The results are shown in Figure 1 .
[0056] Figure 1 It can be seen from the test results that the oxygen index of the fire retardant coatings prepared in Examples 1-3 is significantly lower than that of Comparative Examples 1-3. This indicates that the fire retardant coatings prepared in Examples 1-3 have more excellent fire retardant properties.
[0057] Embodiment 1-3 is to prepare the intercalation modified calcium-based bentonite flame retardant by modifying calcium-based bentonite with guanyl urea phosphate. On the one hand, the guanyl urea phosphate group undergoes ion exchange between the calcium-based bentonite layers, which increases the interlayer spacing of the calcium-based bentonite, greatly improving the thermal stability of the coating, and forming a more stable carbon layer during the combustion process. When a fire occurs, the carbon layer can effectively prevent heat transfer and slow down the combustion rate, thereby improving the flame retardant effect. On the other hand, the synergistic flame retardant effect of nitrogen-phosphorus flame retardant and calcium-based bentonite in the flame retardant further enhances the flame retardant performance.
[0058] At the same time, the silane coupling agent in the coating can form a layer of tight hydrophobic structure on the surface of the coating, so that the surface of the coating has good hydrophobic properties. Nano silicon dioxide also helps to improve the hydrophobicity of the coating. These factors work together to make the fire retardant coatings prepared in Examples 1-3 have a lower oxygen index, that is, better fire retardancy.
[0059] Comparative Example 1 uses an equal amount of calcium-based bentonite instead of the intercalation modified calcium-based bentonite flame retardant. Since no modification treatment is performed, a stable carbon layer cannot be formed, and the flame retardant effect is poor. Comparative Example 2 uses an equal amount of guanyl phosphate urea instead of the intercalation modified calcium-based bentonite flame retardant. Due to the lack of synergistic effect of calcium-based bentonite, a good flame retardant effect cannot be exerted. Comparative Example 3 does not contain the intercalation modified calcium-based bentonite flame retardant, and its fireproof performance is significantly reduced.
[0060] In summary, Examples 1-3 prepare intercalated modified calcium-based bentonite flame retardants by modifying calcium-based bentonite, and combine the synergistic effect of other ingredients to significantly improve the fire retardant properties of the fire retardant coating.
[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0062] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A composite hydrophobic transparent fire retardant coating for blinds, characterized by: The invention comprises the following components in parts by weight: 15-25 parts of acrylic resin, 3-5 parts of water glass, 2-5 parts of potassium silicate, 3-8 parts of silane coupling agent, 2-6 parts of wetting agent, 1-3 parts of buffer, 3-7 parts of film-forming aid, 5-10 parts of nano silicon dioxide, 10-20 parts of intercalation modified calcium-based bentonite flame retardant, and 80-100 parts of deionized water; The intercalation modified calcium-based bentonite flame retardant is prepared by the following steps: a. Add calcium bentonite to deionized water, stir for 5-10 minutes to evenly disperse the modified bentonite to form a 1-3g / L calcium bentonite suspension, add guanyl urea phosphate to deionized water to obtain a 0.8-1.2g / L guanyl urea phosphate solution, and then place the suspension in a constant temperature water bath at 80°C, slowly dropwise add the guanyl urea phosphate solution under the assistance of ultrasound, react for 2-5 hours, obtain a precipitate, filter out the precipitate, dry it in a vacuum oven at 70-90°C for 12-24 hours, and then grind it into powder, pass it through a 200-mesh sieve, and obtain intercalated modified calcium bentonite; b. The intercalated modified calcium-based bentonite is crushed, mixed with epoxy resin, stirred and heated to 100-120°C, mixed evenly and returned to room temperature, then a curing agent and an accelerator are added, stirred evenly, ultrasonically dispersed for 15-30 minutes, defoamed in a vacuum oven at 70-90°C for 1-3 hours, then cast, demolded, crushed into powder, and sieved through a 200-mesh sieve to obtain the intercalated modified calcium-based bentonite flame retardant.
2. The composite hydrophobic transparent fire retardant coating for blinds according to claim 1, characterized in that: The mass ratio of the calcium-based bentonite suspension to the guanyl phosphate urea solution in step a is 1:2-5.
3. A composite hydrophobic transparent fire retardant coating for blinds according to claim 2, characterized in that: In the step b, the mass ratio of intercalated modified calcium-based bentonite, epoxy resin, curing agent and accelerator is 5-10:1-3:0.1-0.5:0.5-1.
4. The composite hydrophobic transparent fire retardant coating for blinds according to claim 3, characterized in that: The silane coupling agent is one or more of γ-glycidyl trimethoxy silane, γ-aminopropyl triethoxy silane, γ-methacryloxypropyl trimethoxy silane and 3-aminopropyl trimethoxy silane.
5. The composite hydrophobic transparent fire retardant coating for blinds according to claim 4, characterized in that: The wetting agent is one or more of ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, polyether-modified silicone, polysorbate, nonylphenol polyoxyethylene ether and octylphenol polyoxyethylene ether.
6. The composite hydrophobic transparent fire retardant coating for blinds according to claim 5, characterized in that: The buffer is one or more of EDTA, disodium EDTA, diethanolamine and triethanolamine.
7. The composite hydrophobic transparent fire retardant coating for blinds according to claim 6, characterized in that: The film-forming aid is one or more of propylene glycol methyl ether, dipropylene glycol butyl ether, N,N-dimethylformamide and isobutyl alcohol.
8. The composite hydrophobic transparent fire retardant coating for blinds according to claim 7, characterized in that: The curing agent is one of methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride and trimellitic anhydride glyceride.
9. The composite hydrophobic transparent fire retardant coating for blinds according to claim 8, characterized in that: The accelerator is one of triethylenetetramine, diethylenetriamine, N,N-dimethylaniline and N,N-dimethylbenzylamine.
10. The composite hydrophobic transparent fire retardant coating for blinds according to claim 9, characterized in that: The fire retardant coating is applied in the production of semi-finished products of venetian blinds, and comprises the following steps: putting solid wood chips into a high-temperature tank, soaking them in the fire retardant coating for 10 hours, then taking the chips out of the tank, and then performing processes such as airing, sorting, cutting, rolling, puttying, and painting to complete the production of the venetian blinds.
Citation Information
Patent Citations
Nano-composite material applied in ship manufacturing
CN108504253A
Fireproof coating with high-temperature resistance and preparation method of fireproof coating
CN108641551A